THE EPISTEMOLOGY OF HEART-MIND IN THE SPIRITUAL TEACHINGS OF MUHYIDDIN IBN ‘ARABI - Yiangou, Nikos (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
Ibn â€˜Arabi off ers a unique framework for explaining the structures of knowledge. His epistemology is referenced within the Oneness of Being (wahdÄt al-wujÅ«d), and all knowledge is ultimately the knowledge that the Being has of Itself through Its own self-disclosure. The human form mirrors this self-disclosure, and within this form he situates the center of the human experience in the faculty of the heart (qalb). Through interactions with the faculties of mind, refl ection and imagination, he provides a robust model for an epistemology that explains the workings of mind and the creation of the many beliefs about God. He intimates at the highest human potential which is the immediate perception of the Real as It appears to the heart in every moment, a condition of complete union known as the â€˜Station of No Stationâ€™. The demands of post-modern thought insist on epistemologies that honor relativism by granting the multiplicity their ontological status. Additionally, the emergent paradigm suggested by integral studies suggests a holistic view of human development that builds on a vision of integrated body, mind and spirit. Ibn â€˜Arabiâ€™s epistemology is singularly capable of addressing these issues as he outlines the timeless structures and processes that comprise human sentience.